Ground penetrating radar survey for structural assessment of a heritage sport building. Issue 1 (November 2020) - Terenzi, G; Fuso, E; Spinelli, P; Costoli, I; Pieraccini, M; Miccinesi, L
Abstract: In order to prevent seismic damage on building heritage built before Seismic Standards, constructions require to be assess to verify the structural response in the case of multi-level intensity seismic actions. This problem especially concerns those buildings with a social function as schools, hospitals, etc., or with historical and architectural value as that designed by important builders of the past. This is the case of the bar-restaurant building of "Bellariva" Sport Centre, designed and built in Florence by the World-famous Italian engineer Pier Luigi Nervi in the Sixty years. Its structure is characterized by reinforced concrete frames and hosts the locker rooms of the swimming pool and a bar on the first floor, a restaurant on the second, where a long crack was observed. The presence of a large balcony with heavy perimeter planters near the cracked zone motivated the execution of on-site tests finalized to determine the steel bars connecting the restaurant floor to the balcony. A Ground Penetrating Radar survey was performed in order to determine the internal structure of the floor, dimensions and disposition of steel bars, and to gather information about the connections between perimeter beams and balcony at the level of the restaurant. The experimental campaign allowed to refine a computational Finite Element Model that was utilized for the performance analysis of the structure in the current state. The paper presents the main results of a preliminary seismic analysis carried out on the structure, on the basis of which some retrofit intervention are suggested.